IEEE International Symposium on Information Theory, 2003. Proceedings. 2003
DOI: 10.1109/isit.2003.1228219
|View full text |Cite
|
Sign up to set email alerts
|

Multiplicity assignments for algebraic soft-decoding of reed-solomon codes

Abstract: A soft-decision decoding algorithm for ReedSolomon codes was recently proposed in [2]. This algorithm converts probabilities observed at the channel output into algebraic interpolation conditions, specified in terms of a multiplicity matrix M. Koetter-Vardy [2] show that the probability of decoding failure is given by h { S M 5 A ( M ) } , where SM is a random variable and A ( M ) is a known function of M . They then compute the multiplicity matrix M that maximizes the e q e c t e d value of SM. Here, we attem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2006
2006
2008
2008

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 2 publications
0
26
0
Order By: Relevance
“…Other algorithms of [10] and [11] minimize the error probability directly. The algorithm of [10] (Gauss) assumes a Gaussian distribution of the score, while that of [11] (Chernoff) minimizes a Chernoff bound on the error probability. The later appears to have the best performance.…”
Section: Algebraic Soft Decodingmentioning
confidence: 99%
See 3 more Smart Citations
“…Other algorithms of [10] and [11] minimize the error probability directly. The algorithm of [10] (Gauss) assumes a Gaussian distribution of the score, while that of [11] (Chernoff) minimizes a Chernoff bound on the error probability. The later appears to have the best performance.…”
Section: Algebraic Soft Decodingmentioning
confidence: 99%
“…These permutations may also be required for the JN algorithm. Then, the relative reduction in complexity is (10) For example, if we assume that on average , a simple calculation for the code over shows that the relative reduction in the complexity of the GE step is about 75%. In practice is close to one.…”
Section: )mentioning
confidence: 99%
See 2 more Smart Citations
“…They also showed that for codes of infinite length the best way to choose the value of m is by making it proportional to the soft information available for each point. In [6], [7] and [8] there were presented some multiplicity assignment strategies which were optimized for infinite-length codes through complex numeric algorithms. However for codes of finite length, an optimum multiplicity assignment strategy is still an open problem.…”
Section: Introductionmentioning
confidence: 99%